2017
DOI: 10.1007/s00464-017-5593-y
|View full text |Cite
|
Sign up to set email alerts
|

Minimally invasive distal pancreatectomy: greatest benefit for the frail

Abstract: OBJECTIVE The benefits of minimally invasive distal pancreatectomy (MIDP) over open surgery continue to be investigated. Frailty is a known predictor of postoperative outcome. We hypothesized that the benefit of minimally invasive distal pancreatectomy is greatest for the frailest of patients. METHODS Data from the pancreas-targeted National Surgical Quality Improvement Program (NSQIP) database for 2014 were reviewed. A modified frailty index (mFI) with 11 preoperative variables previously validated for use … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 33 publications
1
15
0
1
Order By: Relevance
“…This manuscript's strength is that for the first time, the comparison between MIDP and ODP in elderly patients was performed through a propensity score matching to reduce the selection bias. This study is also the first to apply the mFI to a single-center, homogeneous cohort of elderly patients undergoing DP (the report by Konstantinidis et al [ 22 ] is a registry-based study). Some limitations may flaw the results and the considerations: (i) the sample size of elderly who underwent MIDP is small; (ii) a selection bias (the percentage of elderly submitted to MIDP is approximately only 20 percent of the total of elderly underwent DP during the study period).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This manuscript's strength is that for the first time, the comparison between MIDP and ODP in elderly patients was performed through a propensity score matching to reduce the selection bias. This study is also the first to apply the mFI to a single-center, homogeneous cohort of elderly patients undergoing DP (the report by Konstantinidis et al [ 22 ] is a registry-based study). Some limitations may flaw the results and the considerations: (i) the sample size of elderly who underwent MIDP is small; (ii) a selection bias (the percentage of elderly submitted to MIDP is approximately only 20 percent of the total of elderly underwent DP during the study period).…”
Section: Discussionmentioning
confidence: 99%
“…When the final diagnosis was of malignancy, Ca 19–9 values and neoadjuvant therapy were added. According to the mFI, patients were stratified into non-frail (mFI = 0), mildly frail (mFI = 1–2), or severely-frail (mFI > 2), as proposed by Konstantinidis et al [ 22 ]. This stratification was applied to the whole cohort of patients ≥70 years who underwent distal pancreatectomy, and matching was not used due to the small sample size of the MIDP group.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, the LEOPARD-2 trial was interrupted early because of safety concerns due to a disproportionally high number of deaths in the LPD arm [124] , while the PADULAP trial reported a lower major complication rate and a shorter LOS and similar oncological outcomes [125] . No major differences in outcomes have been reported between LPD and RPD [126,127] . In view of existing evidence, the Miami Guidelines concluded that insufficient data exist to recommend MIPD over OPD.…”
Section: Pancreaticoduodenectomymentioning
confidence: 94%
“…There are a number of reported benefits for patients, including lower estimated blood loss, shorter length of functional recovery, and improved short‐term quality of life, which were recently demonstrated in a randomized controlled trial 7 . The MIS approach can also mitigate complication severity in the frail 9 …”
Section: Introductionmentioning
confidence: 99%